Strategic human resource management - Tang, Guiyao; Wei, Li-Qun (New Jersey World Scientific, 2024)
Strategic human resource management (SHRM), as a crucial foundation for the survival and development of a firm, linking human resource management with a firm's strategic objectives to achieve sustainable competitive advantage. Numerous studies and practices have proven that the implementation of SHRM is conducive to acquiring core competitiveness and boosting competitive advantage. In response to the changes that are taking place in HRM practices, it is absolutely necessary for students and managers to learn SHRM systematically.

The book is divided into two parts. The first part of Strategic Human Resource Management introduces related concepts and the relevant theoretical basis of SHRM. The second part focuses on strategic implementation, examining strategic human resource planning, strategic human resources staffing, strategic human resource training and development, strategic performance management and strategic compensation management. The book not only outlines the basic concepts and main contents of SHRM from a strategic standpoint, but underlines the role of latest enterprise practice development and academic frontier research results. Thus, this book is essential reading for anyone interested in the SHRM: from undergraduates and graduate students to master of business administration and firm managers.
Chapter 1 Introduction to strategic human resource management -- Chapter 2 Strategic human resource planning -- Chapter 3 Strategic human resource staffing -- Chapter 4 Strategic human resource training and development -- Chapter 5 Strategic performance management -- Chapter 6 Strategic compensation managemen -- Index.
Includes bibliographical references and index.
Keywords: Personnel management; Strategic planning; Human capital